Geology of the Älgliden Cu-Ni-Au mineralization, northern Sweden - Filoche, Cécile (2009)
The Älgliden intrusion is situated in the northern part of the Skellefte district, hosted by the older stage of the Jörn Granitoid Complex. This intrusion is a mafic dike-like body composed of gabbroic rocks, olivine- bearing toward the centre. Several lenses of massive pyrrhotite ± chalcopyrite are located in the northern and southern parts of the dike, in the middle of the intrusion surrounded by a disseminated mineralization of pyrrhotite ± chalcopyrite. The geochemical data indicate a comagmatic suite, differentiated from a basaltic magma. This magma was probably carrying sulphide droplets differentiated from a larger magma body at depth, but may also have segregated more sulphide liquid as the result of fractional crystallization, contamination and temperature drop. The immiscible sulphide droplets were then concentrated toward the centre by a flow differentiation phenomenon. The dike was emplaced at the interface between a marine domain to the south and a continental domain to the north, presumably a continental volcanic arc. The magma was led by a weaker zone in the country rock created in a local extension context. The Älgliden dike shows strong similarities with several other mafic intrusions or volcanic rocks of the same age, that sometimes also host Cu-Ni mineralizations. This possibly suggests a common source for theses rocks that took part in a larger magmatic system comparable, at a smaller scale, to flood basalts. The Älgliden dike would be one of the numerous feeder dikes of such a magmatic complex, and an exceptional case, since it was able to reach sulphur saturation, and then to segregate and accumulate sulphides. Validerat; 20101217 (root)